OPTIONS FOR LINKING INDONESIA INTO THE TRANSITION RAILWAY NETWORK - , HOTMA PARULIAN LUMBANTORUAN, Prof. Dr. Ir. Siti Malkhamah, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Trans Asian Railway is a mega project aiming to integrate the railway network across the Asia Pacific region. However, there are many issues that must be addressed. The obvious problems are the missing links due to geographical conditions and the difference in the track gauge system. Indonesia, Singapore and Malaysia, separated by Malacca Strait, are three countries in South East Asia that have committed to join and support this project. . This thesis will discuss the best corridor to link the railway network in Indonesia and Malaysia or Singapore that crosses the strait. There are five criteria developed in this thesis, namely risk of natural hazard, travel time, capacity, connectivity and construction costs. The analysis will be using Multi Criteria Analysis (MCA) to choose the best route from six available options. Regarding the break of gauge, transhipment is considered as the most suitable solution along this line based on cost and handling time consideration. Based on the analysis, Route I.1 has the highest score. This route extends from Dumai City â bridge to Rupat Island â passing through the eastern part of Rupat Island. From Rupat Island to Tanjung Tuan, Malaysia, the transportation will be linked by bridge, and finally reaches the Malaysia railway network at Port Dickson. The bridge across Malacca Strait will be designed with long span Suspension Bridge in the middle to accommodate the busy sea traffic in both direction.